2021
DOI: 10.1002/jbt.22712
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Asiatic acid on cell proliferation and DNA damage in vitro and in vivo systems

Abstract: Asiatic acid (AA) is a triterpene with promising pharmacological activity. In the present study, in vitro and in vivo assays were conducted to understand the effect of AA on cell proliferation and genomic instability. AA was cytotoxic to human tumor cell lines (M059J, HeLa, and MCF‐7), with IC50 values ranging from 13.91 to 111.72 µM. In the case of M059J, AA exhibited selective cytotoxicity after 48 h of treatment (IC50 = 24 µM), decreasing the percentage of cells in the G0/G1 phase, increasing the percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Asiaticoside, madecassoside, and their sapogenin triterpene acids such as asiatic acid and madecassic acid are the most noticeable triterpenes present in C. asiatica. (Idris et al, 2021;Lu et al, 2021;Nouri et al, 2021;Ribeiro et al, 2021;Songvut et al, 2021;Sabaragamuwa et al, 2022) Polypharmacological properties of asiatic acid and asiaticoside sparked interest in the research community. Numerous researchers throughout the globe reported the different pharmacological properties of the active phytoconstituents such as anti-inflammatory, antioxidant, hepatoprotective properties, anti-diabetic properties, analgesic, antibacterial, cytotoxic, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asiaticoside, madecassoside, and their sapogenin triterpene acids such as asiatic acid and madecassic acid are the most noticeable triterpenes present in C. asiatica. (Idris et al, 2021;Lu et al, 2021;Nouri et al, 2021;Ribeiro et al, 2021;Songvut et al, 2021;Sabaragamuwa et al, 2022) Polypharmacological properties of asiatic acid and asiaticoside sparked interest in the research community. Numerous researchers throughout the globe reported the different pharmacological properties of the active phytoconstituents such as anti-inflammatory, antioxidant, hepatoprotective properties, anti-diabetic properties, analgesic, antibacterial, cytotoxic, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers throughout the globe reported the different pharmacological properties of the active phytoconstituents such as anti-inflammatory, antioxidant, hepatoprotective properties, anti-diabetic properties, analgesic, antibacterial, cytotoxic, etc. (Lu et al, 2021;Pingyod et al, 2021;Ribeiro et al, 2021;Thong et al, 2021;Mohammed et al, 2022). These pharmacological activities associated with the asiatic acid and asiaticoside has been thoroughly studied and well documented.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] and has attracted recent attention regarding its diverse pharmacological properties including anti-inflammatory activity, 10 the promotion of wound healing, 11 neuroprotection, 12 and anti-cancer activity. 7,13,14 Studies have reported anti-cancer activities of AA that include inducing cell apoptosis by inhibiting cancer cell proliferation, 15 increasing endoplasmic reticulum (ER) stress, 16 and increasing reactive oxygen species (ROS) production. 17 Furthermore, AA demonstrates significant potential in impeding cancer cell metastasis by suppressing their migration and invasion capabilities and decreasing angiogenesis.…”
mentioning
confidence: 99%